Hunting Criminals in Cyberspace: Investigative Strategies for the Digital Era - Tejas D Vodeyar (AG Volumes, 2026)
The digital technologies, interdependencies, and Internet services are rapidly expanding, creating a serious challenge for cybercrime. This review provides an overview of the evolving cybercrime environment and the investigative methods used to detect, investigate, analyze, and prosecute cyber criminals in the digital age. It covers common types of cybercrime, the digital investigation process, and how digital forensics can be used to collect, preserve and analyze digital evidence. The review also emphasizes on new investigation techniques such as Open Source Intelligence (OSINT), Network and Malware Analysis, Artificial Intelligence and international cooperation in the context of Indian cybercrime environment. Also, it provides solutions to key issues like privacy, cloud computing, anonymous communication and jurisdiction. The review identifies the need for the adoption of innovative forensic tools, the use of standardized investigation protocols, and the collaboration between countries to improve cybercrime investigations and digital justice.